Evaluation of Fire Hazard Management - I Nyoman Arya (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Fire is a disaster event that originates from an unwanted fire and can cause losses. Decree of the Minister of Manpower Republic of Indonesia Number. 186 / MEN / 1999 concerning Fire Fighting in the workplace, so that fire hazards can be prevented and avoided as early as possible. This study aims to evaluate the readiness of fire prevention in PT. X through observational with cross sectional approach. The population in this study were all production employees at PT. X as many as 90 people. Data collection is done by using questionnaires, observations and examinations. Data processing is done by descriptive analysis and correlation using the Spearman test. The results of the study the relationship between age and knowledge of employees have a weak relationship (ρs = -0.340), the relationship between training and knowledge of employees has a moderate relationship (ρs = 0.350), the relationship between the length of service of respondents with the level of knowledge in fire preparedness in PT. X is in the weak category (ρs = 0.089), and the relationship between socialization and application of fire prevention procedures and readiness with the knowledge of employees at PT. X is in the weak category (ρs = -0.127), while the observation results of the inspection of infrastructure obtained APAR (73.3%), fire hydrants, fire alarms, detectors, sprinklers (0%) because the equipment was not installed at PT. X, meeting place (100%), exit signs (50%), emergency stairs and emergency exits (0%). Implementation of fire hazard preparedness in PT. X can work well if all elements of the fire hazard control system are implemented thoroughly